Perancangan Master Plan di Objek Wisata Watu Payung sebagai Bentuk Gerakan Desa Sadar Lingkungan dan Fasilitas Umum di Desa Girisuko - Prasetyo Jati, Didit Gunawan (Jurnal Atma Inovasia, 2022)
The results of the 105 group KKN provide a program that can be applied in Girisuko Village, Panggang District, Gunung Kidul Regency, Yogyakarta Special Region. The program given by the group at Girisuko Village is "Village Movement with Environmental Awareness and Public Facilities in Girisuko Village". The purpose of this movement is to increase the awareness of the residents of Girisuko Village, the surrounding environment and the public facilities that exist there. The background of the procurement of this program is because in Girisuko Village there is village potential in the form of natural tourism which is very interesting to visit. This tourism object is a tourist attraction Watu Payung. The geographical location of Girisuko Village in Gunung Kidul Regency adds to the Watu Payung tourist attraction with great potential to become a tourist destination that many tourists can be proud of and visit. Seeing this potential opportunity, the 105th group hopes to increase the potential of the Tourism Village through the Environmental Awareness Village Movement and Public Facilities program.